PERAN ‘ILLAT DALAM IJTIHAD HUKUM ISLAM - ., Agus Hermanto (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
“The Role Of Illat In Islam’s Judging Law”. ‘Illat is a trait that her allegedly contained legal purposes. al-Maqasid al-Shari’ah is to protect religion, soul, mind, wealth and honor. The purpose of the law is an abstract thing, can not be observed, it is necessary ‘illat as a benchmark presence and absence of beneficiaries Basically beneficiaries is built on four principles, namely; 1) Intellect solely be able to know about the benefit and dangers, 2) Benefit is an independent proposition regardless of the texts, 3) The sphere of charity  beneficiaries are mu’amalah and custom fields not worship and muqaddarah). 4) Benefit is the argument of the most powerful Islamic law.Keywords: ‘illat, istinbath, hukum Islam